1994
DOI: 10.1007/bf01739911
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial colonisation withXanthomonas maltophilia — A retrospective study in a cystic fibrosis patient population

Abstract: Xanthomonas maltophilia was isolated from 25 of 150 patients with cystic fibrosis during a period of 10 years (1983-1992). Twelve patients harboured X. maltophilia chronically, i.e. repeatedly for more than 6 months. No predisposing factors for the colonisation could be identified by studying the clinical and laboratory data of the patients, including preceding and concurrent bacterial colonisation with other bacteria, antibacterial treatments, pulmonary function and biochemical markers. Up to 2 years after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 22 publications
3
48
0
1
Order By: Relevance
“…The intermittent delivery of aerosolized tobramycin by a nebulizer (cycles of 300 mg tobramycin or taste-masked placebo twice daily for 28 days followed by 28 days without treatment) did not increase the selection of tobramycin-resistant S. maltophilia and resulted in persistent treatment-emergent S. maltophilia in a very low number of patients (43,276). A retrospective study of tobramycin in two placebo-controlled trials revealed that most S. maltophilia isolates occurred intermittently and were rarely persistent isolates (131); this occasional appearance of S. maltophilia in CF patients has been reported by several studies (76,168,338). As S. maltophilia has been recovered from nebulizers of CF patients (80,157), a small study tested the biofilm-forming abilities of environmental and clinical S. maltophilia isolates after exposure to tobramycin at a concentration (16,000 g/ml) found inside the nebulizers (234).…”
Section: New Treatment Strategiesmentioning
confidence: 68%
“…The intermittent delivery of aerosolized tobramycin by a nebulizer (cycles of 300 mg tobramycin or taste-masked placebo twice daily for 28 days followed by 28 days without treatment) did not increase the selection of tobramycin-resistant S. maltophilia and resulted in persistent treatment-emergent S. maltophilia in a very low number of patients (43,276). A retrospective study of tobramycin in two placebo-controlled trials revealed that most S. maltophilia isolates occurred intermittently and were rarely persistent isolates (131); this occasional appearance of S. maltophilia in CF patients has been reported by several studies (76,168,338). As S. maltophilia has been recovered from nebulizers of CF patients (80,157), a small study tested the biofilm-forming abilities of environmental and clinical S. maltophilia isolates after exposure to tobramycin at a concentration (16,000 g/ml) found inside the nebulizers (234).…”
Section: New Treatment Strategiesmentioning
confidence: 68%
“…The risk associated with the use of inhaled antibiotics is not yet fully known. The trials investigating the efficacy and safety of the use of inhaled tobramycin have shown increases in mic values over time, but this did not correlate with therapeutic success 42 . In another cohort study however, the use of inhaled tobramycin was an independent risk factor for acquisition of multiple antibiotic resistant P. aeruginosa (marpa).…”
Section: Clinical Implications In Cfmentioning
confidence: 97%
“…It has been reported that S. maltophilia negatively impacts cf lung function 42 . In a number of case-control and cohort studies, S. maltophilia positive patients did generally have decreased respiratory virus season.…”
Section: Clinical Impactmentioning
confidence: 99%
“…An increasing incidence of S. maltophilia isolates has been reported in some CF centers during the last decade (2,9,15,22,30). In the United States, the frequency of S. maltophilia isolation from CF patients increased rapidly, from around 3% in 1993 to 12.1% in 2006 (21).…”
mentioning
confidence: 99%